Pembelajaran daring untuk siswa kelas V SD pada materi bercerita dengan menggunakan media wayang kertas - Setyaningsih, Retno; Putu Arga, Hana Sakura; Setiyadi, Ruli (COLLASE (Creative of Learning Students Elementary Education), 2025)
AbstractThe purpose of this qualitative descriptive research is to examine the scenario and implementation, the responses of teachers and students of grade 5 elementary school, students' difficulties experienced, and teacher’s problems in online learning on storytelling material using paper puppets. This study uses test instruments, in the form of pre-test and post-test activities, and non-test instruments, in the form of interviews, observations, and questionnaires. The results showed that the scenario and implementation of the storytelling material using paper puppets went very well, the teacher carried out every step of interactive online learning. This learning also received a positive response from the teacher, as seen from the development of the technological media used. The attitude of students who are enthusiastic in participating in learning and completing assignments well is a positive response from students. Some students have difficulty in storytelling, especially in intonation, expression, using the property, and creativity. When online learning, teachers find some problems like internet network, and it can make the study so disturbed, and in storytelling using paper puppets the teacher must be able to prepare property that can make a student creative. From the results of research and discussion, it can be concluded that storytelling using paper puppets can be implemented by online learning because it can give positive results for teachers and students.Keywords: Online learning, Storytelling, Paper PuppetsAbstrakTujuan dari penelitian deskriptif kualitatif ini untuk menelaah skenario dan implementasi, respon guru dan siswa kelas V SD, kesulitan yang dialami siswa, dan kendala yang dialami guru dalam pembelajaran daring pada materi bercerita dengan menggunakan media wayang kertas. Penelitian ini menggunakan instrumen tes, yang berupa kegiatan pre-test dan post-test, dan instrumen non-tes, berupa wawancara, observasi, dan angket. Hasil penelitian menunjukkan bahwa skenario dan implementasi pada materi bercerita dengan menggunakan media wayang kertas berjalan sangat baik, guru melaksanakan setiap langkah pembelajaran daring yang interaktif . Pembelajaran ini juga mendapat respon yang positif dari guru, terlihat dari pengembangan media teknologi yang digunakan. Sikap siswa yang antusias dalam mengikuti pembelajaran dan menyelesaikan tugas dengan baik, merupakan respon positif dari siswa. Beberapa siswa merasa kesulitan dalam bercerita, terutama pada aspek intonasi, ekspresi, penggunaan media, dan pengembangan kreativitas. Selama pembelajaran daring, guru mengalami kendala berupa jaringan internet yang tidak merata setiap siswa, sehingga dalam penyampaian pembelajaran terhambat, sedangkan pada materi bercerita menggunakan media wayang kertas guru harus mampu mempersiapkan media pembelajaran yang dapat memancing kreativitas siswa. Dari hasil penelitian dan pembahasan dapat disimpulkan jika materi bercerita dengan menggunakan media wayang kertas dapat disampaikan secara daring, karena dapat memberikan hasil positif bagi guru dan siswa.Kata kunci : Pembelajaran daring, Bercerita, Media Wayang Kertas